The Life and Times of Betty Boop: The 100-Year History of an Animated Icon - Benjaminson, Peter (Rowman & Littlefield Publishers, 2023)
From the moment she uttered her first “boop-oop-a-doop!” in 1930, Betty Boop secured her place in history and in the hearts of countless fans. Whether spreading joy during the Depression, thwarting Hitler, running for US president, or flaunting sexual mores, Betty has always been a true American original, embodying and commenting on the culture and attitudes of her time for nearly a century. The Life and Times of Betty Boop is a lively account of the first female, fully human cartoon character, beginning with her creation by the rebellious and innovative young artists of Fleischer Studios, an upstart animation shop intent on competing with Disney. Author Peter Benjaminson traces Betty’s remarkable evolution (originally a dog character, she only gradually became the chanteuse we know today) and dives into the lawsuit that entertainer Helen Kane brought against the Fleischers for allegedly appropriating her image—only for it to come to light that Kane had herself lifted her act from various Black performers. Benjaminson follows Betty through successive historical eras, rebelling against Hollywood’s censorious Hays Code, finding her own path as a self-starting feminist icon, and spawning a merchandising empire that includes everything from watches to wine to Thanksgiving Day floats. Throughout, he shows how, for all her transformations, Betty’s verve and pluck have made her the object of enduring affection.